A relationship between world oil prices and Philippine mining and oil sector index: A comparative study of multivariate GARCH approaches - Chan, Errol Stephen Santos (Animo Repository, 2022)
This research assesses the price movements of world oil prices and Philippine mining and oil sector covering the period from 2017 to July 2022 and comprehended their implications for the oil and mining industries in the Philippines. The Dickey Fuller, McLeod-Li, and Ljung box tests were used in order to ensure that the data used are significant to the study, and the models used to support this study consists of BEKK-GARCH, DCC-GARCH, and cDCC-GARCH. The results show that the world oil prices are strongly associated with the Philippine Mining and Oil Sector Index (PMINI) as Johansen's test specifically revealed that the returns on PMINI exhibit a strong correlation with the returns on the WTI, BRENT, and OPEC prices over the long run. The BEKK-GARCH is found to have inadequate fit based on the Ljung-Box, McLeod-Li, and ARCH tests while the variables resulted in a dynamic relationship with the DCC and cDCC GARCH. Conclusively, the cDCC-GARCH model is found to provide the best fit, based on the three tests. The findings of the study show the dynamic correlation between the PMINI and the aforementioned oil benchmarks notably in times of a crisis and this analysis may serve as a guide for future researchers, policymakers, and institutions to structure contingency and detection systems to prepare for such crises again in the future.